The Cultural and Creative Industries: Organisational and Spatial Challenges to their Governance - Pratt, Andy C. (DIE ERDE – Journal of the Geographical Society of Berlin, 2013)
The Cultural and Creative Industries (CCI) have a distinct geography, one that is dynamic and that has until recently been poorly documented and underexplained. The aim of this paper is to briefly review the changing terrain of analyses of the CCI in order to turn an analytic focus onto the challenge of policy-making in the field of the cultural and creative industries. The structure of the paper follows four steps. First, we outline the shifting nature of governance in nation states and regions; second, we highlight the corresponding shifts occurring in the organisation of the cultural and creative industries, and the field of cultural policy; third, we consider the need to resolve governance and the cultural and creative industries. Finally, we outline some responses to this challenge.